HDAC6 inhibitor-loaded brain-targeted nanocarrier-mediated neuroprotection in methamphetamine-driven Parkinson's disease - Khang-Yen Pham; Shristi Khanal; Ganesh Bohara; Nikesh Rimal; Sang-Hoon Song; Thoa Thi Kim Nguyen; In-Sun Hong; Jinkyung Cho; Jong-Sun Kang; Sooyeun Lee; Dong-Young Choi; Simmyung Yook (Redox Biology)
The dynamic equilibrium between acetylation and deacetylation is vital for cellular homeostasis. Parkinson's disease (PD), a neurodegenerative disorder marked by α-synuclein (α-syn) accumulation and dopaminergic neuron loss in the substantia nigra, is associated with a disruption of this balance. Therefore, correcting this imbalance with histone deacetylase (HDAC) inhibitors represents a promising treatment strategy for PD. CAY10603 (CAY) is a potent and selective HDAC6 inhibitor. However, because of its poor water solubility and short biological half-life, it faces clinical limitations. Herein, we engineered lactoferrin-decorated CAY-loaded poly(lactic-co-glycolic acid) nanoparticles (denoted as PLGA@CAY@Lf NPs) to effectively counter methamphetamine (Meth)-induced PD. PLGA@CAY@Lf NPs showed enhanced blood–brain barrier crossing and significant brain accumulation. Notably, CAY released from PLGA@CAY@Lf NPs restored the disrupted acetylation balance in PD, resulting in neuroprotection by reversing mitochondrial dysfunction, suppressing reactive oxygen species, and inhibiting α-syn accumulation. Additionally, PLGA@CAY@Lf NPs treatment normalized dopamine and tyrosine hydroxylase levels, reduced neuroinflammation, and improved behavioral impairments. These findings underscore the potential of PLGA@CAY@Lf NPs in treating Meth-induced PD and suggest that an innovative HDAC6-inhibitor-based strategy can be used to treat PD.